Epidemiological analysis of contraceptive methods in the public health network of a city in western Paraná (Research, Society and Development, 2023)
Objective: To evaluate which contraceptive methods are the most sought after by the female population in the public health network in the city of Cascavel-PR. Methods: Epidemiological study that was obtained from data provided by the Municipal Health Department of Cascavel-PR on contraceptive methods offered in the municipality. Results: The result showed that over the years (2018 to 2022) the demand for a contraceptive method has been increasing, being the most sought-after method the pill of Levonorgestrel 0.15mg + Ethinylestradiol 0.03mg, soon followed by Medroxyprogesterone 150mg/ml injectable, next the Norethisterone Enanthate 50mg/ml + Estradiol Valerate 5mg/ml injectable and, lastly, of these 4 methods analyzed the copper IUD. Conclusions: The demand for contraceptive methods has been growing in Cascavel in recent years, which reflects the demographic growth of the city. The pill is the most sought method in absolute value, but in recent years has been losing space to contraceptive methods and injectable intrauterine devices, given its ease of administration and greater access to information from the female population of Cascavel-PR.